2021
DOI: 10.1016/j.apnr.2021.151416
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' occupational satisfaction during Covid-19 pandemic

Abstract: Background Covid-19 has brought healthcare workers in general and nurses in particular into the limelight as never before. It is important to study the intensity of the impact of this pandemic on the profession. Objective This study aims to assess the occupational satisfaction during the pandemic of Covid-19 among the nurses in Israel, to shed light on conditions of work and to identify factors associated with low occupational satisfaction. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 21 publications
8
84
1
8
Order By: Relevance
“…HCWs who lack PPE reported lower occupational satisfaction than those who did not [113,117]. To increase the HCWs' satisfaction rates, their accomplishments at the pandemic were found to be positively associated with higher occupational satisfaction rates [117]. Moreover, as mentioned earlier, the better the performance of communication dimension, including the psychological support, will raise the HCWs' job satisfaction and lower the rates of burnout and stress [110,117].…”
Section: The Hcws-centeredness Dimensionmentioning
confidence: 82%
See 2 more Smart Citations
“…HCWs who lack PPE reported lower occupational satisfaction than those who did not [113,117]. To increase the HCWs' satisfaction rates, their accomplishments at the pandemic were found to be positively associated with higher occupational satisfaction rates [117]. Moreover, as mentioned earlier, the better the performance of communication dimension, including the psychological support, will raise the HCWs' job satisfaction and lower the rates of burnout and stress [110,117].…”
Section: The Hcws-centeredness Dimensionmentioning
confidence: 82%
“…A study [113] showed that the prevalence of burnout among physicians was found to be (57.7%) in the pandemic, which is considered so high. HCWs who lack PPE reported lower occupational satisfaction than those who did not [113,117]. To increase the HCWs' satisfaction rates, their accomplishments at the pandemic were found to be positively associated with higher occupational satisfaction rates [117].…”
Section: The Hcws-centeredness Dimensionmentioning
confidence: 94%
See 1 more Smart Citation
“…Present findings suggest that job satisfaction could be enhanced by providing health professionals with opportunities for happiness with work. These may span across aspects that were previously identified as contributing to physicians’ and nurses’ job satisfaction, including higher remuneration, good relationship with colleagues and patients, increase in work autonomy, task diversification, professional growth, time efficiency, adequate staffing, as well as safety and protective personal equipment as highlighted during the pandemic [ 4 , 9 11 , 32 , 34 ]. However, such a comprehensive intervention—though highly welcome—may not be realistic considering the dearth of resources and the challenges healthcare systems are facing worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Poor level job satisfaction among healthcare workers during the COVID-19 pandemic has been reported in several studies worldwide. Mean occupational satisfaction of 3.6 (score range, 1-5) was reported during the COVID-19 pandemic among Israeli nurses[ 60 ]. Job satisfaction score of 2.8 (out of a possible score of 4) was reported in a large-scale study among healthcare workers in Italy[ 61 ].…”
Section: Job Satisfaction and Turnover Intentionmentioning
confidence: 99%